Review on lightweight hardware architectures for the crypt-analytics in FPGA - Tappari, Sunitha; Sridevi, K. (International Journal of Engineering and Technology, 2018)
Internet of Things (IoT) plays a vital role in the Wireless sensor networks (WSNs), which is used for many applications, such as military, health, and environmental. Security is the major concern and it is very difficult to achieve because of a different kind of attack in the network. In recent years, many authors have introduced different Hardware Architectures to solve these security problems. This paper has discussed about a review of various Hardware Architectures for the lightweight Crypt-analytics methods and the comparative learning of various Crypt-analytics and authentication systems carried out. The comparative study result showed that the lightweight algorithms have good per-formance compared to the conventional Crypt-analytics algorithm in terms of memory requirement, operations, and power consumption.Â